PARLIAMENTARY OVERSIGHT IN ROMANIA, A GUARANTEE OF ACHIEVING SEPARATION OF POWERS IN THE STATE - SILVIA MIHALCEA (Challenges of the Knowledge Society)
This paper focuses on the dimension of the relationships between the Parliament and other state institutions in Romania (Government, chief of state, public administration authorities) from the point of view of the parliamentary oversight. The reason and the necessity of the parliamentary oversight comes naturally from the existence of the democratic principle of representation: using the mandate entrusted by the people in the electoral elections, the members of the Parliament are entitled and, in the first place, have the obligation to verify the public affairs related to the safeguarding of the national interest and achievement of the well being. This mechanism is a flexible one and involves collaboration, cooperation, balance and thus, it appears as the strongest form in accomplishing the separation of powers in the state. The paper approaches the early developments and the evolution of the parliamentary oversight, the wide range of tools used by the Parliament to carry out this function (procedures and forms) according to the stipulations of the Constitution, laws and European Treaties and emphasizes the role of the parliamentary practice in this field. The study also puts forward a series of detailed recommendations aiming to improve the quality of this act. A new element is the parliamentary oversight in the field of European affairs, introduced by the implementation of the Lisbon Treaty, which consolidates the role of the national assemblies in order for them to become important actors in the European construction by their active involvement in the decision making.